(untitled) (Mantichora. Italian Journal of Performance Studies, 2020)
This essay suggests the possibility of an approach capable of identifying the more radically naturalistic profile of photographic performativity, and, thus, of its ontological specificity: a bio-aesthetics of photography. By assuming that forms of knowledge and human mental processes are always the common background common for any cognitive activity, the specificity of this proposal is developed through an evolutionary hypothesis of functional cognitive ergonomics. In this perspective, arts are not the gradual development of media technologies and photography – in which all modern visual media productions are included –, can be considered the more complex evolution of media technologies applied to symbolic needs.